2011
DOI: 10.1007/s11033-011-1180-9
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of single cell derived human mesenchymal stem cells into cells with a neuronal phenotype: RNA and microRNA expression profile

Abstract: The adult bone marrow contains a subset of non-haematopoietic cells referred to as bone marrow mesenchymal stem cells (BMSCs). Mesenchymal stem cells (MSCs) have attracted immense research interest in the field of regenerative medicine due to their ability to be cultured for successive passages and multi-lineage differentiation. The molecular mechanisms governing the self-renewal and differentiation of MSCs remain largely unknown. In a previous paper we demonstrated the ability to induce human clonal MSCs to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 82 publications
0
13
0
Order By: Relevance
“…5B). Additional studies demonstrate that number of CD114+ upregulated microRNAs (miR-25, 106b, 17, 18, 19, 20a, 143, 27) are repressed upon neuronal lineage differentiation of somatic stem cells (33, 35, 36). In addition, microRNA pathway analysis with two independent prediction platforms (DIANA (DIANA Lab, Athens, Greece) and Ingenuity (Ingenuity Systems, Redwood City, CA) each demonstrated enrichment of p53, NGF, Notch and additional signaling pathways driving differentiation of neuronal and neural crest lineages (Supplementary Table S4 and Supplementary Table S5).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…5B). Additional studies demonstrate that number of CD114+ upregulated microRNAs (miR-25, 106b, 17, 18, 19, 20a, 143, 27) are repressed upon neuronal lineage differentiation of somatic stem cells (33, 35, 36). In addition, microRNA pathway analysis with two independent prediction platforms (DIANA (DIANA Lab, Athens, Greece) and Ingenuity (Ingenuity Systems, Redwood City, CA) each demonstrated enrichment of p53, NGF, Notch and additional signaling pathways driving differentiation of neuronal and neural crest lineages (Supplementary Table S4 and Supplementary Table S5).…”
Section: Resultsmentioning
confidence: 99%
“…MicroRNAs play an important role in reprogramming and stem cell maintenance and recent studies have identified a number of microRNAs which regulate neuronal lineage specification from embryonic precursors (33, 34). To evaluate differential microRNA expression, we performed small-RNA sequencing on RNA directly isolated from FACS-purified CD114+ and CD114− subpopulations from three neuroblastoma cell lines (NGP, IMR-32, LA-N-5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, there have been multiple reports that MSCs engage in extensive exchange of vesicles containing micro-RNAs during differentiation of the cells (Crobu et al, 2011; Zhang et al, 2011) and in their interaction with malignant cells (Gregory et al, 2011). (For recent review see Guo et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Tenascin-cytotactin (TN-C), highly expressed in the subventricular zone, generates a stem cell “niche” that acts to orchestrate neural stem cell development in mice [23,24]. Among transdifferentiation studies, most have been conducted with animal cells [2528] and some with human MPCs [29,30]. …”
Section: Introductionmentioning
confidence: 99%